Implementasi Sanksi Ekonomi Pemerintah Inggris Terhadap Rusia di Liga Sepak Bola Inggris pada Tahun 2022-2023 - Yudhistira, Evantio; Arisanto, Puguh Toko (Frequency of International Relations (FETRIAN), 2025)
This study examines the targeted economic sanctions (smart sanctions) imposed by the UK Government on Russian-affiliated actors in the English Premier League during the 2022–2023 period, in response to Russia’s invasion of Ukraine. Using a descriptive-analytical qualitative approach, the study explores how international economic sanctions became closely linked to the world of professional football and highlights the concept of issue linkage, particularly negative linkage, in international relations. The UK Government imposed sanctions including asset freezes, restrictions on ownership and new investments, termination of sponsorship agreements, and limitations on financial services targeting clubs affiliated with Russia, such as Chelsea FC, Everton FC, and Arsenal FC. These sanctions caused financial instability, disrupted commercial operations, and led to changes in club ownership. The study also finds that the pressure from these sanctions prompted both the UK Government and the Premier League to strengthen regulations on foreign ownership transparency and investment oversight, marking a shift toward stricter control in the English football industry.